Problems faced by antiretroviral (ARV) drug users in Kathmandu Valley. - Karki, Jyoti (2014)
ABSTRACT: Problem Statement:Inability to achieve adherence even after 3 decades of ARV introduction is a matter as it hides a list of problems which needs to be addressed. Objective|: The study aims to assess the problems faced by antiretroviral drug users attending ART centers of Kathmandu. Methodology: A descriptive study was carried out in Shukraraj Tropical and Infectious Disease Control Hospital(STIDCH), Teku, and Bir Hospital from 18th of Bhadra, 2071. A total of 82 samples were collected from these centres. Non-probability convenience sampling was used to recruit respondents and semi-structured questionnaire tool was developed for the interview to find out the problems faced by antiretroviral drug users in Kathmandu Valley. Results: The overall problems faced by ART users in valley includes dealing with side-effects (65.9%) long waiting time to get services (24.4%), unsatisfactory services 94.9%), geographical barrier (69.3%), financial barrier (25.6%), etc. Few were turned off from social/religious (70.7%) and recreational activities (51.2%). Absence of disclosure 914.6%), lack of spousal support (10.9%), humiliation (34.1%), etc. were present. Stigmatization materializes as having to be lose job (8.5%),feeling ashamed of diagnosis (30.5%), feeling isolated in groups (34.1%), etc . Adherence towards medicine was found to be 86.5%. Conclusion: ART is a long term process and to achieve it rationally, a user has to cope with lots of problem, associated not only with own physical health but also with the outcomes of psychosocial brutality because of stigma and discrimination. Further worsening of the situation is due to financial constraints. Identification and analysis of those problems is the only key to address them reasonably and hence achieving the goal of ART. Policy making, planning and delivery of services seek improvement in various steps. Awareness is another demand to end psych-social discrimination to the ART users.